2005
DOI: 10.2337/diabetes.54.4.1000
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Null Male Mice Develop Late-Onset Obesity Caused by Decreased Energy Expenditure and Lipolytic Activity but Show Normal Insulin Sensitivity With High Adiponectin Secretion

Abstract: Androgen receptor (AR) null male mice (AR L؊/Y ) revealed late-onset obesity, which was confirmed by computed tomography-based body composition analysis. AR L؊/Y mice were euphagic compared with the wild-type male (AR X/Y ) controls, but they were also less dynamic and consumed less oxygen. Transcript profiling indicated that AR L؊/Y mice had lower transcripts for the thermogenetic uncoupling protein 1, which was subsequently found to be ligand-dependently activated by AR. We also found enhanced secretion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
212
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(244 citation statements)
references
References 44 publications
24
212
2
Order By: Relevance
“…Another consequence of central AR gene invalidation was the alteration of the sexually dimorphic somatotropic axis. A transient decrease in body weight was described in ubiquitous ARKO mice, but it was reversed since 12 weeks of age due to the increased adipose tissue mass and decreased lipolytic activity Fan et al, 2005). In AR NesCre males, growth retardation was persistent until 20 -30 weeks of age.…”
Section: Discussionmentioning
confidence: 97%
“…Another consequence of central AR gene invalidation was the alteration of the sexually dimorphic somatotropic axis. A transient decrease in body weight was described in ubiquitous ARKO mice, but it was reversed since 12 weeks of age due to the increased adipose tissue mass and decreased lipolytic activity Fan et al, 2005). In AR NesCre males, growth retardation was persistent until 20 -30 weeks of age.…”
Section: Discussionmentioning
confidence: 97%
“…Triglycerides in retroperitoneal and mesenteric adipose tissue increase after castration in rats but decrease when animals are treated with testosterone (25). Additionally, androgen receptor knockout mice develop late onset obesity through reduced adipose tissue lipolysis in animals of both sexes (16,42). These findings suggest that androgens may be key steroids in the modulation of fat accumulation and distribution in both humans and rodent models.…”
mentioning
confidence: 83%
“…Accordingly, in vitro studies demonstrated that androgens inhibit adipogenic differentiation of mouse or human preadipocytes through an AR-mediated pathway (Singh et al 2006, Gupta et al 2008. By contrast, studies on the relationship between the androgen-AR system and insulin sensitivity produced conflicting results, showing both negative (Sato et al 2003, Fan et al 2005 and positive (Lin et al 2005) effects.…”
Section: Introductionmentioning
confidence: 93%
“…The results from ARKO models revealed that AR plays an important role in male metabolism, by affecting the energy balance and lipolysis (Sato et al 2003, Fan et al 2005. A negative effect of AR activation on visceral adiposity has been clearly demonstrated in ARKO mice (Yanase et al 2008).…”
Section: Introductionmentioning
confidence: 93%